2014
DOI: 10.1074/jbc.m113.527085
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Substance P Binding Sites on the Neurokinin-1 Receptor Using Genetic Incorporation of a Photoreactive Amino Acid

Abstract: Background: Unnatural amino acids can be genetically incorporated into 7-transmembrane receptors. Results: A photoreactive amino acid introduced into the neurokinin-1 receptor cross-links substance P to the N-terminal and extracellular loop II domains of the receptor. Conclusion:The extracellular domain of the neurokinin-1 receptor possesses multiple potential binding sites for substance P. Significance: A photocross-linking methodology reveals novel interaction sites in the neurokinin-1-receptor-substance P c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 49 publications
(82 reference statements)
0
39
0
Order By: Relevance
“…SP in conjunction with NMDA-receptor activation induces gene expression that facilitates synaptic changes that eventually lead to longlasting potentiation. SP shows preferential binding to the ligandbinding site of NK1 receptors (37). Binding of SP to NK1 receptors leads to activation of adenylyl cyclase, hydrolysis of phosphoinositides, mobilization of intracellular calcium ions, and activation of downstream effector molecules such as PKA, PKC, and MAPK (38), all of which have been associated with the expression of LTP (39).…”
Section: Discussionmentioning
confidence: 99%
“…SP in conjunction with NMDA-receptor activation induces gene expression that facilitates synaptic changes that eventually lead to longlasting potentiation. SP shows preferential binding to the ligandbinding site of NK1 receptors (37). Binding of SP to NK1 receptors leads to activation of adenylyl cyclase, hydrolysis of phosphoinositides, mobilization of intracellular calcium ions, and activation of downstream effector molecules such as PKA, PKC, and MAPK (38), all of which have been associated with the expression of LTP (39).…”
Section: Discussionmentioning
confidence: 99%
“…These finding suggest that all three receptors possess specific binding sites for both SP and QWF. Site directed mutagenesis studies of NK-1R demonstrated that amino acid residues 23–25 (NQF) in the receptor’s amino terminus along with H 108 (third transmembrane domain), F 268 (sixth transmembrane domain), Y 287 (7 th transmembrane domain) are important for binding substance P [5658]. Furthermore, histidine at position 197 (H 197 ) in the fifth transmembrane helix of human NK-1R binds specifically to the non-peptide receptor antagonist CP 96345 to block SP action [59].…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Following a peripheral tissue injury, it was demonstrated that SP and SP C‐terminal fragments (i.e. SP 3–11 , SP 5–11 and SP 8–11 ) have an agonist effect on the NK1R (Maggi, ; Michael‐Titus, Blackburn, Connolly, Priestley, & Whelpton, ; Myöhänen, Venäläinen, Garcia‐Horsman, & Männistö, ; Valentin‐Hansen et al, ). We therefore suspect that NKA fragments may also play an essential role in nociception.…”
Section: Resultsmentioning
confidence: 99%
“…Following a peripheral tissue injury, it was demonstrated that SP and SP C-terminal fragments (i.e. SP [3][4][5][6][7][8][9][10][11] ) have an agonist effect on the NK1R (Maggi, 1995;Michael-Titus, Blackburn, Connolly, Priestley, & Whelpton, 1999;Myöhänen, Venäläinen, Garcia-Horsman, & Männistö, 2008;Valentin-Hansen et al, 2014).…”
Section: Detection Of Npk and Nka Peptide Fragmentsmentioning
confidence: 99%